An Introduction to a Head and Neck Cancer‐Specific Frailty Index and Its Clinical Implications in Elderly Patients: A Prospective Observational Study Focusing on Respiratory and Swallowing Functions. (1st July 2016) - Kwon, Minsu; Kim, Shin‐Ae; Roh, Jong‐Lyel; Lee, Sang‐Wook; Kim, Sung‐Bae; Choi, Seung‐Ho; Nam, Soon Yuhl; Kim, Sang Yoon
Abstract : Introduction: Frailty refers to a decreased physiologic reserve in geriatric patients and its importance in terms of treatment planning and outcome prediction has been emphasized in oncologic practices for older patients with cancer. We investigated the clinical implications of a head and neck cancer (HNC)‐specific frailty index suggested by prospective clinical and functional evaluations of HNC patients. Materials and Methods: We analyzed data on 165 elderly patients with HNC who were prospectively enrolled in our hospital from 2010 to 2013. Pretreatment functional evaluations were performed according to all comprehensive geriatric assessment (CGA) domains. We additionally evaluated the patients' respiratory and swallowing functions using pulmonary function tests, voice handicap index (VHI), MD Anderson Dysphagia Inventory (MDADI), and other associated tests. Factors affecting the 2‐year morbidity and mortality were also analyzed. Results: Respiratory and swallowing problems were major causes of 2‐year morbidity. Pretreatment performance status, VHI ≥8, MDADI <70, dental problems, and chemotherapy were significantly associated with early morbidity and mortality (all p < .05). CGA‐assessed frailty was found in 72 patients (43.6%) and was significantly associated with 2‐year mortality ( p = .027) but not with morbidity ( p = .716). The high‐risk group according to our new HNC‐specific frailty index that included functional evaluations of respiration and swallowing showed significantly higher 2‐year morbidity ( p = .043) and mortality ( p < .001). Conclusion: Pretreatment functional disabilities related to respiration and swallowing were significantly associated with early morbidity and mortality. The suggested index would be more useful for assessing frailty in elderly HNC patients. Implications for Practice: This study is the first report in terms of suggesting a new frailty index focusing on respiratory and swallowing functions in elderly patients with head and neck cancer. This study shows that functional disabilities associated with respiration and swallowing significantly affected early morbidity and mortality in these elderly patients. The head and neck cancer‐specific frailty index described in this report, which includes functional evaluations of respiration and swallowing, significantly predicted both early morbidity and mortality. Abstract : The clinical implications of a head and neck cancer (HNC)‐specific frailty index focusing on respiratory and swallowing functions were investigated in 165 elderly patients with HNC. Pretreatment functional disabilities related to respiration and swallowing were significantly associated with early morbidity and mortality.